A Pragmatic Analysis of Proxemics as A Nonverbal Communicator with Reference to The Concept of Social Distancing During Covid-19 Pandemic - Muhammad, Himdad Abdullqahar; Mahmood , Rauf Kareem (Zanco Journal of Human Sciences, 2021)
The term ‘social distancing’ has been widely used recently in various means of mass communication to encourage people to keep it as a way of preventing the spread of Covid-19 Coronavirus. In addition to studies in natural sciences, the term ‘social distancing’ could also be explored in various research areas in humanities, including pragmatics, sociology, and psychology. This paper deals with the pragmatic reading of the term ‘social distancing’ with reference to proxemics as a nonverbal communicator to find out whether or not genuine social distancing could result in weakening ties among the members of any given community. By analyzing the connection between ‘social distancing’ and context, proxemics, spatial deixis, power and solidarity, the paper hypothesizes that the term ‘physical distancing’ is a more appropriate preventive approach to substitute for ‘social distancing’, while retaining social integration during the pandemic.